Research Progress and the Development Trend of the Utilization of Crop Straw Biomass Resources in China - Yang, Wei; Li, Xiaohua; Zhang, Yutao (Frontiers in Chemistry, 2022)
The utilization of crop straw biomass resources is highly emphasized by governments and academia in recent decades. Based on the core databases of the literature in China National Knowledge Infrastructure (CNKI) academic journals, CiteSpace software is used to analyze and process the hotspots, and this study proposed the primary coverage and evolutionary trends of research on the utilization of crop straw resources. The thesis proposes the research development trend for improving the institutional mechanism of the utilization of crop straw resources, strengthening technology research and development, exploring the economic model of green cycle agriculture, accelerating the construction of the industrial system, and designing new paths of resource utilization in multiple ways, which helps estimate the development trend of the utilization of crop straw resources and provide inspiration and direction for future research and practices.